1989
DOI: 10.1136/adc.64.7.997
|View full text |Cite
|
Sign up to set email alerts
|

Do education groups help diabetics and their parents?

Abstract: SUMMARY The importance of education in the management of diabetes is recognised but has rarely been assessed in children. In a longitudinal controlled study we have examined the effect of a programme of education on the knowledge, diet, and concentration of glycated haemoglobin A1c in a group of diabetics. The programme took the form of two packages of education each consisting of four weekly meetings, in which small groups of parents and older children were led in a discussion of different aspects of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Thirteen studies involved children with Type 1 diabetes [9,15–17,19–21,27–32]. The average age of participants was approximately 10 years; however, wide ranges within studies were noted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies involved children with Type 1 diabetes [9,15–17,19–21,27–32]. The average age of participants was approximately 10 years; however, wide ranges within studies were noted.…”
Section: Resultsmentioning
confidence: 99%
“…To be included in the meta‐analysis for the knowledge category (parent scores only), the authors had to report outcomes specifically related to diabetes knowledge (general, treatment, or care). When more than one intervention group was compared with control [9,19–21], we chose the intervention theoretically most effective. We stratified studies a priori by follow‐up interval: < 3 months, 6–12 months [22], or > 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with previous findings. 22,23,39 In addition, results indicated that the educational needs of father caregivers are unrelated to disease duration; rather, they appear to be linked to the developmental stage of the child. For example, participants with teenage children with T1DM identified more topics, on average, than their counterparts with school-age children regardless of length of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…13,[21][22][23] The educational needs of today's fathers are unknown and likely differ from participants in these earlier studies, and there is no currently available diabetes educational intervention that takes into account that most fathers will likely be more effectively reached outside the clinic. 7 One way to reach fathers outside the clinical setting is through the use of the Internet or mobile technology.…”
Section: Discussionmentioning
confidence: 99%
“…This audit showed that in our practice, there is a need to improve these aspects of epilepsy management. These tasks would be easier in a clinic dedicated to children with epilepsy and indeed such`education clinics' have been well described for other conditions such as diabetes (Hackett et al 1989). A patient support group under the guidance of an epilepsy nurse specialist, is another way that further information about epilepsy can be disseminated.…”
Section: Discussionmentioning
confidence: 99%